2017
DOI: 10.1016/j.jenvrad.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Natural radionuclides in lichens, mosses and ferns in a thermal power plant and in an adjacent coal mine area in southern Brazil

Abstract: The radio-elements U,U, U,Th, Th andPo were characterized in lichens, mosses and ferns species sampled in an adjacent coal mine area at Figueira City, Paraná State, Brazil, due to their importance for the assessment of human exposure related to the natural radioactivity. The coal is geologically associated with a uranium deposit and has been used as a fossil fuel in a thermal power plant in the city. Samples were initially prepared at LABIDRO (Isotopes and Hydrochemistry Laboratory), UNESP, Rio Claro (SP), Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 58 publications
3
11
0
Order By: Relevance
“…CF= C sample / C reference (1) The enrichment degree of the metal can be classified as follows: no enrichment (CF≤1), minor enrichment (1<CF≤3), moderate enrichment (3<CF≤5), moderately severe enrichment (5<CF≤10), and severe enrichment (CF>10) [6,11]. Fig.…”
Section: Metal Deposition On Moss Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…CF= C sample / C reference (1) The enrichment degree of the metal can be classified as follows: no enrichment (CF≤1), minor enrichment (1<CF≤3), moderate enrichment (3<CF≤5), moderately severe enrichment (5<CF≤10), and severe enrichment (CF>10) [6,11]. Fig.…”
Section: Metal Deposition On Moss Samplesmentioning
confidence: 99%
“…Therefore, moss biomonitoring was used as a complementary technique alongside classic instrumental methods in air pollution detection and control. Also, mosses have been used as bioindicators for terrestrial long-lived radionuclides ( 40 K, 238 U, and 232 Th) and artificial radionuclides ( 137 Cs, 90 Sr, and 239+240 Pu) in the environment [1][2][3][4][5].Rapid industrialization in cities and the contributory relationships with the original pollution sources can cause serious environmental problems within cities [6][7][8][9]. Istanbul is the most crowded city in Turkey and the fifth most crowded in the world.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lichens are symbiotic organism composed of fungi and algae that are well known to incorporate and store a variety of radionuclides derived from both natural origins, like U-238, Ra-226, Th-232 etc. in mine areas [1,2], and artificial origins such as atmospheric nuclear weapon tests and nuclear power plant accidents [3][4][5][6][7]. Lichens are recognized as useful biomonitoring tools because of having the following features: (i) they are widely distributed in terrestrial ecosystems and found on various substrata such as rock, tree, soil, artificial man-made structures, and so on, (ⅱ) they can accumulate metals including radionuclides directly absorbing from air into the body, due to their lack of root system and protective outer cuticle, (ⅲ) they have high accumulation capacities of pollutants on the large surface areas of thalli, and (ⅳ) they have longevity due to their slow metabolic activity and slow growth rate throughout the year [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Reviews and reports indicate the use of mosses (Ares et al, 2012) for lead and 210Pb (Galhardi et al, 2017;Kosior et al, 2017) as NORM retention indicators in ecosystems (Reszka and Wołoszyn, 2007;Shotyk et al, 2015). Grodzinskaya recently published an extensive overview of tree NORM and heavy metal levels in city parks and streets in Kyiv, Ukraine (Grodzinskaya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%